Impact of cancer on school, work, and financial independence among adolescents and young adults. Issue 19 (13th July 2020) - Sisk, Bryan A.; Fasciano, Karen; Block, Susan D.; Mack, Jennifer W.
Abstract : Background: For adolescents and young adults (AYAs), the diagnosis of cancer can impede social development, especially with respect to education, employment, and financial independence. However, there are limited quantitative data on the extent and trajectory of life disruptions during cancer treatment for AYA patients. Methods: This was a longitudinal, prospective, questionnaire‐based cohort study of 145 AYA patients with cancer aged 15 to 29 years who were treated at a large academic cancer center. Questionnaires were administered shortly after diagnosis and 4 and 12 months after diagnosis. Results: Although half of the participants lived with their parents 6 months before diagnosis, 61% lived with their parents after diagnosis ( P  = .0002 vs 6 months before diagnosis), with a similar proportion reported to be living with their parents 4 months after diagnosis (61%; P  = .001) and 55% doing so 12 months after diagnosis ( P  = .07). Before diagnosis, 38% of the patients were not attending school. After diagnosis, that proportion rose to 61% ( P  < .0001), with a similar proportion 4 months after diagnosis (61%; P  < .0001); 54% were not in school at 12 months ( P  = .001). Patients experienced similar decrements in employment (30% not working before diagnosis vs 49% not working after diagnosis; P  < .0001) and financial independence (37% with complete financial independence before diagnosis vs 31% after diagnosis; P  = .02). Overall, 65% of the patients (94 of 145) had not returned to their precancer baseline in at least 1 of these 4 social domains by 12 months after diagnosis. Conclusions: For many AYA patients, cancer leads to less engagement with school and work activities and decreased financial independence from parents. Clinicians should engage in early and ongoing discussions with patients about the potential impact of cancer on their lives. Abstract : For many adolescent and young adult patients, the diagnosis of cancer leads to less engagement with school and work activities and decreased financial independence from their parents. These interruptions to their developing lives persist throughout the year after diagnosis.